(untitled) - Harbison, Elmore Harris (Ithaca, N.Y., 1955)
With the aid of over sixty important sources, most of them translated and abridged by the author, this brief history brings an age of upheaval into sharp focus. It succinctly shows how a compelling ideology, the Christian faith, shaped the history of the Reformation. The religious revolution of the sixteenth century shattered an ecclesiastical structure and quickened a universal faith. The Christian heritage that the Reformation revitalized and transmitted to our time is still the source of western man's ability to talk in terms of universal justice, humanity, and the rights of man.
Keywords: Reformation